THE EFFECT OF GLOBALIZATION IN CORRUPTION ERADICATION THROUGH WHISTLEBLOWER (ECONOMIC ANALYSIS OF LAW) - Marpaung, Zaid Alfauza; Rokan, Mustafa Kamal; Zulham, Zulham (AS-SAIS (JURNAL HUKUM TATA NEGARA/SIYASAH), 2025)
This article aims to discuss the influence of globalization in the eradication of corruption through whistleblowers and is reviewed from the economic analysis of law. The type of research used is normative law, with an approach to laws and regulations and legal concepts. Data sources were obtained from primary, secondary and thesis legal materials which were then analyzed qualitatively. The results of the study concluded that the eradication of corruption in Indonesia was influenced by the globalization of law. This can be seen from Indonesia's participation in the international agreement United Nations Convention Against Corruption (UNCAC) which was later ratified into Law Number 7 of 2006. The substance of UNCAC includes requiring States parties to include in their national legal systems the protection of whistleblowers. The transplantation of UNCAC law into the national legal system is contained in the provisions of Article 10 of Law Number 31 of 2014 concerning the Protection of Witnesses and Victims. From the perspective of economic analysis, the role of whistleblowers in providing information is quite effective and efficient in dismantling corruption. In general, law enforcement has difficulty in uncovering corruption cases, even spending considerable resources and costs in handling them. This is due to the characteristics of corruption crimes that are carried out in a hidden, organized manner and difficult to uncover. Whistleblower  information is very helpful for law enforcement, saving resources and costs in the disclosure process. On the other hand, the state also gains profits because corrupt actors are caught and return state losses. Therefore, cost and benefit, whistleblowers need to be rewarded and protected.Keywords: Globalization, Corruption, Whistleblower, Economic Analysis, Law